Combined effects of lung function, blood gases and kidney function on the exacerbation risk in stable COPD: Results from the COSYCONET cohort. (July 2019) - Trudzinski, F.C.; Kahnert, K.; Vogelmeier, C.F.; Alter, P.; Seiler, F.; Fähndrich, S.; Watz, H.; Welte, T.; Speer, T.; Zewinger, S.; Biertz, F.; Kauczor, H.-U.; et al.
Abstract: Rationale: Alterations of acid-base metabolism are an important outcome predictor in acute exacerbations of COPD, whereas sufficient metabolic compensation and adequate renal function are associated with decreased mortality. In stable COPD there is, however, only limited information on the combined role of acid-base balance, blood gases, renal and respiratory function on exacerbation risk grading. Methods: We used baseline data of the COPD cohort COSYCONET, applying linear and logistic regression analyses, the results of which were implemented into a comprehensive structural equation model. As most informative parameters it comprised the estimated glomerular filtration rate (eGFR), lung function defined via forced expiratory volume in 1 s (FEV1 ), intrathoracic gas volume (ITGV) and (diffusing capacity for carbon monoxide (DLCO), moreover arterial oxygen content (CaO2 ), partial pressure of oxygen (PaCO2 ), base exess (BE) and exacerbation risk according to GOLD criteria. All measures were adjusted for age, gender, body-mass index, the current smoking status and pack years. Results: 1506 patients with stable COPD (GOLD grade 1–4; mean age 64.5 ± 8.1 y; mean FEV1 54 ± 18 %predicted, mean eGFR 82.3 ± 16.9 mL/min/1.73 m 2 ) were included. BE was linked to eGFR, lung function and PaCO2 and played a role as indirect predictor of exacerbation risk via these measures; moreover, eGFR was directly linked to exacerbation risk. These associations remained significant after taking into account medication (diuretics, oral and inhaled corticosteroids), whereby corticosteroids had effects on exacerbation risk and lung function, diuretics on eGFR, BE and lung function. Conclusion: Even in stable COPD acid-base metabolism plays a key integrative role in COPD risk assessment despite rather small deviations from normality. It partially mediates the effects of impairments in kidney function, which are also directly linked to exacerbation risk.